(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The article examines the development of the image of the “little man” in Russian literature—from the classical works of the 19th century to the texts of contemporary authors. Special attention is given to how the interpretation of this type of character changes depending on the historical and cultural context. It is shown that, while preserving its key features, this image acquires new semantic nuances.